Addressing Violence Against Women and Children Through the 'Lapor Pak 129' Innovation - Pusparini, Rani (Universitas Airlangga, 2024)
Abstract This study aims to elucidate the service innovations implemented by the Office of Women's Empowerment and Child Protection and Population of the East Java Provincial Government to provide protection against violence towards women through the LAPOR PAK 129 innovation. The number of complaints of violence against women and children is quite high. Therefore, the Office of Women's Empowerment and Child Protection and Population of East Java Province developed this innovation to address the issue. It serves not only as a platform for receiving complaints of violence against children and women but also provides health services, social rehabilitation services, legal aid and enforcement services, as well as repatriation and social reintegration services. This study employs a qualitative method. Data collection techniques include interviews, observations, and document studies. This study applies interactive data analysis. The results of the